2015
DOI: 10.3109/07853890.2014.982064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body weight on efficacy and safety of direct oral anticoagulants in the treatment of patients with acute venous thromboembolism: A meta-analysis of randomized controlled trials

Abstract: Results of our meta-analysis suggested that DOACs might be a safe and effective therapeutic option for the treatment of acute VTE even in the patients with extreme body weights. However, other studies with larger study populations are warranted to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…94 Two other Class III meta-analyses were conducted to compare the safety and efficacy of NOACs in the treatment of VTE (ie, DVT or PE) 95,96 ; both included 6 phase 3 randomized controlled trials [87][88][89]92,98,100 and showed that there was no significant difference between the NOACs in regard to the risk of recurrent VTE, mortality, or safety. The fourth Class III meta-analysis by Di Minno et al 97 included the same 6 studies as above and showed similar safety and efficacy of treatment with NOACs versus VKA among patients of various body weights.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…94 Two other Class III meta-analyses were conducted to compare the safety and efficacy of NOACs in the treatment of VTE (ie, DVT or PE) 95,96 ; both included 6 phase 3 randomized controlled trials [87][88][89]92,98,100 and showed that there was no significant difference between the NOACs in regard to the risk of recurrent VTE, mortality, or safety. The fourth Class III meta-analysis by Di Minno et al 97 included the same 6 studies as above and showed similar safety and efficacy of treatment with NOACs versus VKA among patients of various body weights.…”
Section: Future Researchmentioning
confidence: 99%
“…For this critical question, 3 Class II studies 87-89 and 8 Class III studies [90][91][92][93][94][95][96][97] were identified comparing the efficacy and safety of NOACs with standard therapy in the treatment of acute VTE. All 3 of the Class II studies 87-89 and 3 of the Class III studies 90,91,94 specifically examined outcomes in patients receiving a diagnosis of isolated DVT, whereas the remaining 5 Class III studies 92,93,[95][96][97] examined cohorts that included patients with DVT and PE.…”
Section: Future Researchmentioning
confidence: 99%
“…To our knowledge, this is the largest prospective, observational study that showed EBW effect on clinical outcomes of patients treated with anticoagulation for acute VTE. These results add to the prior literature which compared either rivaroxaban or apixaban outcome in relation to warfarin 3,4,19 or the whole DOAC group compared to warfarin 20,21 . Post hoc analysis of EINSTEIN DVT and EINSTEIN PE trials 19 analyzed clinical outcomes among three bodyweight groups (≤50 kg; > 50 to100 kg, and >100 kg) and four BMI groups (<25, ≥25 to <30, ≥30 to <35, and ≥35 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 72%
“…Major bleeding assessment by weight was not performed in this study 4 . Also, a meta‐analysis including patients from 6 randomized clinical trials for VTE showed similar efficacy and safety of DOAC therapy compared to VKA therapy in patients with EBW compared to “normal” bodyweight group 20 . In the recent retrospective analysis of 366 adult patients with a BMI of at least 40 kg/m 2 who were treated with apixaban, rivaroxaban, or warfarin for VTE treatment, the incidence of recurrent VTE and major bleeding was similar between the three therapeutic groups 21 .…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, for the Xa inhibitors, a normal anti‐Xa assay most likely excludes clinically significant levels of the drug. An anti‐Xa assay that is calibrated for the specific drug in use could be used to estimate the drug level, thus an anti‐Xa assay that is calibrated only for heparin indicates the presence of the drug . Although such recommendations are meant for bleeding episodes in patients taking DOACs, they could also be useful in assessing bleeding risks for patients taking DOACs who need to undergo emergency TPE procedures.…”
Section: Resultsmentioning
confidence: 99%